Interweaving Cultures: A Sociolinguistic Inquiry into Sinhala-English Code-Mixing in Urban Sri Lanka - Hakmana Parana Liyanage Waruni Shashikala (Progress in Language, Literature and Education Research Vol. 8, 2024)
Language mixing has become a natural phenomenon in the spoken discourse of the urban Sinhalese–English bilinguals today. More than twenty decades of contact with a foreign language has resulted in a large number of lexical items being mixed by urban bilingual speakers in Sri Lanka in their daily conversations. This study examines how and why they mix codes from a sociolinguistic perspective and analyzes the structural properties of such code-mixing (CM) found in their speech. This study follows a descriptive qualitative method. This is qualitative since this depends on data that include words, phrases and sentences and is descriptive since it provides an accurate factual description of a setting. The sample comprised 30 bilinguals from the employed bilingual population in the main urban city of Sri Lanka due to their frequent use of the mixed-code in conversation. For a comprehensive analysis of the sociolinguistic aspects of the respondents’ speech, a sociolinguistic questionnaire based on the four discourse strategies: foregrounding, nativization, hybridization, and neutralization as proposed by Kachru (1978/1983/1986) was used. For the structural analysis, their spontaneous speech was recorded, and the framework of Muysken [1]. insertion, alternation, and congruent lexicalization (CL) was used. Results for CM of Sinhala-English participants show a variety of English items integrated into Sinha-la utterances. The findings report that this mixed-variety has evolved due to CM and is undoubtedly the preferred code for expressing neutralization of attitudes in speech. Further, their language choice seems to have been influenced by the age. Structurally, this discussion proves insertion as the major CM strategy in the bilinguals’ spoken variety, while CL is the least used. From a pedagogical perspective, this study proposes CM as a possible communicative strategy to promote interaction among students in the second language learning-teaching context in Sri Lanka. This study suggests that CM can be one of the strategies that EFL/ESL (English as a foreign/second language) teachers use to accommodate the students’ level of proficiency since it makes the learner intake the knowledge provided by the tutor quite comfortably in the classroom.